(untitled) (Itinera, 2015)
The notion of invariance permeates different research areas and often takes on different meanings. In different fields (psychology, phenomenology, physics, and ethics) the invariance concept attempts to explain the mechanisms of perceptual grouping. In this article invariance is considered a structural condition of our way of perceiving music and especially musical improvisation. It helps to understand the relationship between musical improvisation and nonlinearity, i.e. between what is transformed and what remains unchanged in the process of improvisation. I argue that every musical improvisation whose characteristics are nonlinear implies perceptual invariance with respect to time.